Participation Politique Des Femmes Au Niger: Analyse De La Contribution Du Genre Féminin Dans Le Développement Politique - Aboubacar, Zakari (European Scientific Journal, ESJ, 2017)
This research focuses on the political participation of women in Niger. In addition to the documentation on the subject, we conducted interviews with women and political party leaders. Thus, the quest for equality is more than ever a concern of Nigerian women. In this article we asked the following research question: how can we explain the contribution of the feminine gender to political development in Niger? The general objective pursued through this article is to analyze the contribution of women in political development in Niger. To answer the research question and check the general objective the qualitative method through maintenance guides was used. After analyzing the data, the results show that politics is still an exclusively male domain or that there are many institutionalized discriminations, the dominance of political space by men being the rule, although it did not exclude a certain presence women. The results also show that the question of the presence of women in public life in general and political space in particular is a global challenge to harmonize the political space of Niger.